KRG and Arab gulf countries: undifined relations - Zubir Rasool Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The relationship between Kurdistan Region and Gulf countries started only after 2003. These relations have been influenced by Iraq’s place in the political and security calculations of the Gulf countries. After the collapse of Saddam’s regime in 2003, the GCC countries tensions in the region even further increased, due to the imbalance of power against GCC and crisis of government in post 2003 Iraq, as well as the hegemony of Shi’a groups on the Iraqi state. It can be argued that the Gulf countries’ Kurdish card has been linked with two main goals of GCC foreign policy in Iraq. The first goal is related to Saudi Arabia’s objective of playing a major role in the region’s politics and in post-2003 Iraq, in particular as a reaction to increasing role of Iran and Turkey in the regional scene. The second goal is related to Saudi Arabia’s policy of countering Shiite’s domination over Iraqi state, through creating a balance among Iraq’s major components. So far, the KRG and GCC relations are more tactical and reactional rather than strategic, and are linked to Iraq’s negative attitude towards the Gulf Countries. The GCC has approached KRG mostly during the political developments and political crisis in Iraq in order to benefit from the Kurdish weight in Baghdad and play a role in Iraqi domestic policies.